The Effect of Adhesive Types of Damar and Pine Resin for Biobricket Manufacturing from Sugarcane Bagasse - Mentarina Rizki; Safira Mustaqilla; Zuhra Zuhra; Wahyu Rinaldi; T Mukhriza (Journal of Applied Technology, 2022)
Biobriquette is an alternative fuel that is produced using biomass, namely bagasse waste. Bagasse has a high cellulose content of 37.65. The purpose of this biobriquette research was to see the effect of the type of resin adhesive and pine resin using the carbonization method by reviewing the quality of the calorific value, moisture content, compressive strength, and ash content using different ratios of raw materials and adhesives so as to produce good biobriquettes according to with SNI. From the test results, the characteristics of briquettes in the form of calorific values ranged from 7033.70 cal/gr-7878.72 cal/gr where the highest calorific value of resin adhesives, the ratio of raw materials and 50:50% was 7,878.72 cal/g, while the lowest calorific value was at 65:35% mixed adhesive briquettes ie 7,033.70 cal/g. The test results on the compressive strength ranged from 13.15 kg/cm2 to 224.72 kg/cm2 where the highest compressive strength value was 50:50% resin adhesive, which was 244.3 kg/cm2, the lowest compressive strength value was 80:20% mixed adhesive, namely 13.15 kg/cm2. The water content test obtained values ranging from 3.33% to 4.21%, the highest water content of 80:20% pine adhesive was 4.21%, the lowest water content was pine adhesive and 50:50% resin, which was 3.33%. The results of the ash content test ranged from 2.52 g to 4.96 g, the highest ash content of 80:20% mixed adhesive was 4.96% and the lowest ash content was 50:50% pine adhesive briquette which was 2.52%. From all the analyzes that have been carried out, it can be concluded that briquettes using resin adhesive with a ratio of raw materials and adhesives of 50:50% have the best quality compared to other briquettes where the briquettes that have been produced meet the quality of SNI.